Performance and safety of therapeutic erythrocytapheresis in polycythemia and hemochromatosis treatment: single centre experience - Iva Lucija Burnać; Ines Bojanić; Sanja Mazić; Marija Lukić; Branka Golubić Ćepulić (Hematology, Transfusion and Cell Therapy, 2024)
Abstarct: Introduction: Therapeutic erythrocytapheresis has some advantages over therapeutic phlebotomy, the standard treatment for cytoreduction in polycythemia and hemochromatosis. Erythrocytapheresis can be performed on different cell separators, each with its own characteristics. We present our experience of therapeutic erythrocytapheresis in the treatment of polycythemia and hemochromatosis with an analysis of the performance of cytoreduction, and a comparison between the characteristics of intermittent- and continuous-flow cell separators. Material and methods: During a 20-year period, 1731 procedures were performed in 125 patients, 1634 (94.4%) with a Haemonetics MCS+ separator and 97 (5.6%) with a Spectra Optia system device. The performance of cytoreduction using the Haemonetics MCS+ separator was analysed in 442 procedures performed in 56 patients and the performance of the two apheresis devices was compared. Results: Haemoglobin (Hb) and haematocrit (Hct) values were significantly reduced after erythrocytapheresis with the Haemonetics MCS+ device (Hb: 18.69%; Hct: 18.73%; p-values both <0.001). The reductions of Hb and Hct were significantly higher in the Haemonetics MCS+ procedure (p-value <0.001), but the Spectra Optia procedure depleted a significantly higher RBC volume (495 mL versus 442 mL) in a shorter time (18 min versus 36 min). Conclusion: Both the Haemonetics MCS+ and Spectra Optia systems proved to be highly efficient and safe in RBC cytoreduction with short procedure times. Erythrocytapheresis reduces the frequency of necessary procedures thereby justifying its therapeutic use especially in eligible patients of working age.